One Text as Another: Ireland Translated between Languages, Texts and Cultures. - Sanches, Zuzanna (Comparative Critical Studies, 2013)
The article discusses the context of the essay titled "On Language as Such and the Language of Man" by Walter Benjamin which focused on the transcoding model in translation theory. The author stated that translation is a controversial activity, stating its solitary and intrinsically social. The author added that translation can serve as a paradigm for a phenomenon called linguistic hospitality in order to understand the translator's task.